Legislated rights: securing human rights through legislation - Webber, Grégoire C. N. (University Press, 2018)
The important aspects of human wellbeing outlined in human rights instruments and constitutional bills of rights can only be adequately secured as and when they are rendered the object of specific rights and corresponding duties. It is often assumed that the main responsibility for specifying the content of such genuine rights lies with courts. Legislated Rights: Securing Human Rights through Legislation argues against this assumption, by showing how legislatures can and should be at the centre of the practice of human rights. This jointly authored book explores how and why legislatures, being strategically placed within a system of positive law, can help realise human rights through modes of protection that courts cannot provide by way of judicial review.